Sociolinguistic Influence On Kimbab Family Children's Bilingualism On YouTube - Alisha Mulya Wardhani; Otong Setiawan Djuharie (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study examines bilingualism in children within the "Kimbab Family" YouTube channel from a sociolinguistic perspective. The increasing number of bilingual and multilingual individuals globally, as a direct consequence of globalization, highlights the complex cognitive, social, and cultural aspects of bilingualism. In bilingual families, language choices are often shaped by family language policies and social norms, reflecting a speaker's social identity and communication strategies. This research aims to describe and analyze the phenomenon of bilingualism in the Kimbab Family children, specifically identifying patterns of code-switching and code-mixing, and the social factors influencing their language choices. Employing a qualitative descriptive approach, the study uses video content from the "Kimbab Family" YouTube channel as its primary data source, focusing on the verbal utterances of Suji, Yunji, and Jio that exhibit code-switching and code-mixing between Indonesian and Korean. Data collection involves observation, transcription, and systematic notation, while data analysis follows Miles, Huberman, and Saldaña's interactive model, comprising data reduction, data display, and conclusion drawing. The findings indicate that the children's bilingualism is manifested through code-switching, primarily triggered by changes in interlocutor, aligning with communication accommodation theory. Code-mixing, the more frequent phenomenon, is driven by lexical factors (e.g., Korean terms without direct Indonesian equivalents) and expressive factors, demonstrating that both languages function as a unified linguistic system for them. Additionally, the topic of conversation and pragmatic functions significantly influence language choice, reflecting a functional domain separation between the two languages and serving as markers of their hybrid identity.